Governance and Sustainability: The Effects of Ownership, CEO Tenure, and Gender Diversity on CSR Disclosure - Azyyati, Chika Adlina; Helmina, Monica Rahardian Ary (Economics and Business Solutions Journal, 2025)
This study examines the influence of foreign ownership, CEO tenure, and ownership concentration on corporate social responsibility (CSR) disclosure, with board gender diversity as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using a quantitative associative approach, data were collected from 47 purposively sampled companies. CSR disclosure was measured using the CSR Disclosure Index (CSRDI) based on the Global Reporting Initiative (GRI) Standards 2021, while ownership structure and managerial characteristics were measured through secondary data obtained from annual and sustainability reports. Data analysis employed Structural Equation Modeling (SEM) with WarpPLS 7.0 to test the research hypotheses. The results reveal that foreign ownership and ownership concentration have significant positive effects on CSR disclosure, whereas CEO tenure has a significant negative effect. Interestingly, board gender diversity does not significantly moderate the relationships between ownership structure, CEO tenure, and CSR disclosure. These findings contribute to the development of legitimacy theory and stakeholder theory by showing how ownership and leadership characteristics influence disclosure practices in emerging markets. Practically, the study provides implications for regulators and companies in Indonesia to strengthen sustainability governance, improve CSR reporting quality, and encourage meaningful board diversity